Bidoupia phongii, new orchid genus and species (Orchidaceae, Orchidoideae, Goodyerinae) from southern Vietnam - Averyanov, Leonid V.; Ormerod, Paul A.; Duy, Nong Van; Tien, Tran Van; Chen, Tao; Zhang, Dian-Xiang (Phytotaxa, 2016)
Species of subtribe Goodyerinae (Orchidaceae, Orchidoideae) in the flora of Vietnam have been the subject of a series of taxonomic treatments (Seidenfaden 1992, Averyanov 1994, 2008, Averyanov & Averyanova 2003, Nguyen, Averyanov & Duong 2005). Nonetheless, the inventory of this group remains incomplete due to their sporadic distribution, rarity in nature, and deficiency of available herbarium and living collections. Additionally, almost all Goodyera-related species rarely flower either in nature or cultivation, which makes available observations scarce. As a result, new data on species and records for the flora of Vietnam are appearing continuously (Ponert et al. 2014, Averyanov et al. 2016) in addition to the already completed accounts. One more curious novelty from Goodyerinae discovered recently in southern Vietnam is described and illustrated below.